THE INFLUENCE OF DISCIPLINE, MOTIVATION AND WORK FACILITIES ON EMPLOYEE PERFORMANCE - Robi; Syahir Natsir; Yoberth Kornelius (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2023)
This research aims to identify the simultaneous and partial relationship between work discipline, motivation and facilities on employee performance at Bapenda Palu City. The type of this research is descriptive quantitative. The sampling technique in this research is using the census technique (saturated sampling), with a sample of 58 respondents. The types of data are quantitative data and qualitative data. Data sources are primary data and secondary data. Techniques in collecting data are carried out by observation, questionnaires and documentation. The technique in analyzing data is multiple linear regression analysis. The results showed that (1) Discipline, motivation and work facilities have a positive and significant relationship on employee performance at Bapenda Palu City (2) Work discipline has a positive and significant relationship on employee performance at Bapenda Palu City (3) Work motivation has a positive and significant relationship at Bapenda Palu City (4) Work facilities have a positive and significant relationship on employee performance at Bapenda Palu City.